Avaliação do Programa Universidade para Todos, PROUNI, no Curso de Direito na Faculdade Paraíso em Juazeiro do Norte - Ce - Feitoza, Francisca Disnê Candido (2012)
This dissertation deals with the Brazilian public policies that provide access to higher education in Brazil, which were implemented by the federal government from 2005 with the creation of Programa Universidade para Todos- PROUNI for the purpose of positive actions targeted social inclusion the lower classes of Brazilian society that has always been absent from public universities. Shows that the program was implemented by the Ministry of Education - MEC for the purpose of inclusion associated with socio-political tax waiver by the Union, offering full scholarships or partial higher education institutions to the private portions of the population characterized by their situation socioeconomic, ethnic and cultural. The objective of this research was to analyze whether the PROUNI has been fulfilling its role as regards the granting of scholarships is partial or full, the students considered disadvantaged graduates from public schools or private institutions of fellows. The methodology for carrying out this research work was divided into two parts, from the analysis of books, scientific articles, dissertations and theses that deal with the theme, as well as transdisciplinary studies and / or interdisciplinary program dealing with the study. The second part of the research was based on a case study, from interviews with students from the Law Faculty Paraíso. This research spoke about public policy in general, especially to support public policies in education prioritizing those facing higher education, showing that the inclusion of disadvantaged youth at this level of education specifically in Brazilian private institutions at no cost to them, is possible by PROUNI. The survey results showed that the vast majority of beneficiaries have PROUNI family income below two minimum wages which would make access to these private institutions, has made clear the important role of media in publicizing the program thus attracting those who resorted to him; evidenced in the statements of those interviewed his delight to be beneficiaries of the program, making it clear that without this, would not be in law school of the institution locus of the research, stressed that students enrolled at PROUNI found no difficulty in following the course and indicated that the MEC must develop a better systematic monitoring of the program and ensure it is maintained and has expanded its number of vacancies.